Asia and Europe in the 21st Century: New Anxieties, New Opportunities. Edited by Rahul Mishra, Azirah Hashim and Anthony Milner. London and New York: Routledge, Taylor and Francis Group, 2021. - Meena Louis , Yanitha (AEI Insights, 2023)
Book